Pemberdayaan Masyarakat pada Budi Daya dan Pengembangan Produk Pohon Gaharu (Aquilaria sp.) di Kabupaten Tolitoli, Sulawesi Tengah - Triadiati Triadiati; Miftahudin Miftahudin (Agrokreatif: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2021)
Tolitoli District has a potential for agarwood trees in the forests, but it has not been optimally utilized and preserved by the local communities. Therefore, efforts are needed to increase understanding and community involvement in cultivation and product development of agarwood trees. The objectives of this activity are: to explore agarwood tree species in the forest and sources of local inoculums using a purposive sampling method for agarwood production, to assess the suitability of agro-climates for agarwood tree cultivation, to conduct face-to-face training and practice for agarwood tree breeding and bio-induction by injection, and to identify socio-economic conditions to support agarwood tree cultivation for community empowerment through product development and cultivation in Kabupaten Tolitoli. The project was implementated by exploring and identifying the existence of natural agarwood trees and agarwood farmers, training, and mentoring. The results of exploration and identification showed that Kabupaten Tolitoli has natural resources of agarwood trees in the forest and local inoculums for the bio-induction of agarwood formation. Also, the local community, including the local government, practitioners, farmers, and educational institutions, have great interest and desire for product development and cultivation of agarwood trees. Thus, it can be concluded that community empowerment through product development and cultivation of agarwood trees in Kabupaten Tolitoli can be implemented.